1994
DOI: 10.2307/3578906
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Irradiation or Hydrocortisone Treatment of Rats Increases the Proteinase Activity Associated with Histones of Thymus Nuclei

Abstract: An increase in the activity of histone-associated rat thymus nucleus proteinases specific for histones H2A, H2B and H1 was shown after gamma irradiation or hydrocortisone treatment of animals. Histone H1-specific proteinase activity is dependent on DNA and increases in the presence of denatured DNA, whereas proteinases specific for core histones are inhibited in the presence of denatured DNA. The increase in the activity of histone-associated proteinases depends on the radiation dose and the time after irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…One potential interpretation might be that certain signaling events triggered by bum alter interactions among the intracellular molecules involved in histone gene expression. In particular, injury-associated pathophysiologic alterations (e.g., cytokine production, increased proteolytic activity, the induction of glucocorticoids, and oxidative stress) in the thymus may influence the expression of histones (3,8,30,31). It is of interest to note that the altered expression of several histone variant mRNAs in the thymus parallels our previous findings of increases in apoptosis and TNF-(X induction I day after bum (7).…”
Section: Discussionsupporting
confidence: 72%
“…One potential interpretation might be that certain signaling events triggered by bum alter interactions among the intracellular molecules involved in histone gene expression. In particular, injury-associated pathophysiologic alterations (e.g., cytokine production, increased proteolytic activity, the induction of glucocorticoids, and oxidative stress) in the thymus may influence the expression of histones (3,8,30,31). It is of interest to note that the altered expression of several histone variant mRNAs in the thymus parallels our previous findings of increases in apoptosis and TNF-(X induction I day after bum (7).…”
Section: Discussionsupporting
confidence: 72%
“…The biological significance of Rel B cleavage is currently unknown. Thus DNA-PK, PARP, U1-70 kDa, lamins and Rel B, as well as several other nuclear proteins (NuMA, retinoblastoma protein, topoisomerase I and II, and histone H1) which contribute to the maintenance of structural and functional integrity in the nucleus, all represent specific targets for apoptotic proteases including the ICE-like protease(s ) [5,43,70,71,[77][78][79]. The loss of these proteins Wil!…”
Section: Substrates For Apoptotic Proteasesmentioning
confidence: 99%
“…The Lon protease can bind to mtDNA and is apparently involved in the degradation of proteins regulating mtDNA replication and gene expression (Fu and Markovitz, 1998). Earlier we showed that histone H1-specific proteases, which are activated by DNA containing breaks or denatured regions, are tightly bound to thymus nuclear histones (Kutsyi and Gaziev, 1994). The activity of proteases associated with nuclear histones considerably increased in regenerating rat liver in the period of intensive DNA transcription and replication, as well as thymus nuclei under exposure to various factors leading to degradation of DNA (such as γ-radiation and hydrocortisone injection) (Kutsyi et al, 1992;Kutsyi and Gaziev, 1994;Kutsyi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier we showed that histone H1-specific proteases, which are activated by DNA containing breaks or denatured regions, are tightly bound to thymus nuclear histones (Kutsyi and Gaziev, 1994). The activity of proteases associated with nuclear histones considerably increased in regenerating rat liver in the period of intensive DNA transcription and replication, as well as thymus nuclei under exposure to various factors leading to degradation of DNA (such as γ-radiation and hydrocortisone injection) (Kutsyi et al, 1992;Kutsyi and Gaziev, 1994;Kutsyi et al, 2002). By cleaving histone H1 in nuclei, histone-associated proteases are involved in decompacting the highly-ordered chromatin structure, thereby increasing the accessibility of DNA for enzymes involved in DNA transcription, replication, repair, and degradation.…”
Section: Discussionmentioning
confidence: 99%